Software Visualization in the Context of Service-Oriented Architectures - Eicker, Stefan; Spies, Thorsten; Kahl, Christian (Proceedings of the 4th IEEE International Workshop on Visualizing Software for Understanding and Analysis (Vissoft2007), 2007)
Software visualization contributes to the support and maintenance of software systems, especially to alleviating the handling of a systems’ complexity. This article deals with approaches to visualization in the context of service-oriented architectures, which allow the building of flexible system environments, but which are nevertheless subject to a dynamic outer field. Thus a distinctive understanding both from the technological and from the functional point of view is an important prerequisite for a successful implementation of such systems. The following article presents a concept of three-dimensional views as well as the development of a visualization pipeline to create dynamic views. These approaches provide the stakeholders with access to relevant information which can then be integrated into the over-all context.
Keywords: Software visualization; SOA; service-oriented architecture; comprehension; visualization